Aryl λ3‐Iodane‐Mediated 6‐exo‐trig Cyclization to Synthesize Highly Substituted Chiral Morpholines. Issue 13 (11th September 2015) - Kishore Vandavasi, Jaya; Hu, Wan‐Ping; Chandru Senadi, Gopal; Chen, Hui‐Ting; Chen, Hsing‐Yin; Hsieh, Kuang‐Chan; Wang, Jeh‐Jeng
Abstract A mild and efficient transition metal‐free approach has been developed for the synthesis of highly substituted chiral morpholines from alkenols by amino acid‐derived iodine(III) reagents via a 6‐exo‐trig cyclization. The key features of this work include the formation of three chiral centers with a high diastereomeric ratio, broad functional group compatibility, and atom/time economic methodology.